PELAKSANAAN TUGAS DAN WEWENANG POLISI DALAM MENGATASI KERUSUHAN DI STADION KANJURUHAN BERDASARKAN UU DAN PERATURAN KAPOLRI: Police Duties And Authorities To Overcome The Riot At Kanjuruhan Stadium Based On Law And Regulations Of Kapolri - Niky Wahyu Saputra; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2025)
National Police of the Republic of Indonesia is a State Instrument that carries out one of the functions of government, especially in the field of maintaining security and public order. This is regulated in Law No 2 of 2002 concerning the National Police of the Republic of Indonesia. As a guideline in carrying out Polri duties, it is regulated in National Police Chief Regulation No 1 of 2009 concerning the Use of Force in Police Actions which regulates Polri actions within its authority. The problem in this research is what are the duties and authorities of the Indonesian National Police in carrying out crowd control based on Law No 2 of 2002 and National Police Chief Regulation No. 1 of 2009? Are the actions of the Malang Police in dealing with the incident at Kanjuruhan Stadium in accordance with the Law? No 2 of 2002 and National Police Chief Regulation No 1 of 2009. This research is normative research, uses secondary data, is descriptive, qualitatively, and draws conclusions deductively. The duties and authority of the Republic of Indonesia Police in carrying out crowd control are regulated in Articles 13 and 14, while their authority is contained in Articles 15 and 16. And actions of the Malang Police in dealing with incidents are not in line with Article 18 of Law No 2 of 2002 by looking at the level of danger in the regulations. National Police Chief No 1 of 2009 there was no urgency for the police to fire tear gas.